2022
DOI: 10.3389/fnmol.2022.829886
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Mitigates Methamphetamine-Induced Anxiety-Like Behavior Through Ameliorating Mitochondrial Dysfunction and Neuroinflammation

Abstract: Methamphetamine (MA) abuse results in neurotoxic outcomes, including increased anxiety and depression. Studies have reported an association between MA exposure and anxiety, nonetheless, the underlying mechanism remains elusive. In the present study, we developed a mouse model of anxiety-like behavior induced by MA administration. RNA-seq was then performed to profile the gene expression patterns of hippocampus (HIPP), and the differentially expressed genes (DEGs) were significantly enriched in signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 75 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…Our results are in accordance with those of Singh et al, who reported that repeated administration of quercetin (25 and 50 mg/kg) for 9 days suppressed naloxone-precipitated morphine (10 mg/kg) withdrawal [31]. On the other hand, quercetin inhibited nicotinetriggered CPP reinstatement [42], alleviated METH-induced anxiety-like behavior in mice, attenuated the activation of astrocytes, and reduced the levels of IL-1beta and TNF-α, but not IL-6 [43]. In addition, quercetin (10, 30 and 100 mg/kg i.p.)…”
Section: Quercetin Abolished Heroin Dependence Acquisition and Inhibi...supporting
confidence: 91%
“…Our results are in accordance with those of Singh et al, who reported that repeated administration of quercetin (25 and 50 mg/kg) for 9 days suppressed naloxone-precipitated morphine (10 mg/kg) withdrawal [31]. On the other hand, quercetin inhibited nicotinetriggered CPP reinstatement [42], alleviated METH-induced anxiety-like behavior in mice, attenuated the activation of astrocytes, and reduced the levels of IL-1beta and TNF-α, but not IL-6 [43]. In addition, quercetin (10, 30 and 100 mg/kg i.p.)…”
Section: Quercetin Abolished Heroin Dependence Acquisition and Inhibi...supporting
confidence: 91%
“…High levels of ROS have been linked to cell death and degeneration, notably in disorders that include type 2 diabetes, Alzheimer's disease, autism, mood disorders and attention-deficit/hyperactivity disorder (ADHD), among others (Michel et al, 2012). These observations have been expanded in recent studies that demonstrate correlations between mitochondrial dysfunction and various psychiatric disorders (Burtscher et al, 2022;Chen et al, 2022;Umare et al, 2022). In these cases, viruses and bacteria were identified as tightly involved in promoting alterations of mitochondrial and host cellular function via hypoxia and immune-mediated upregulation of inflammatory factors and conditions associated with oxidative stress.…”
Section: Introductionmentioning
confidence: 91%
“…Among them, the anxiolytic effects of quercetin, luteolin and narigenin are closely related to the inhibition of inflammatory response, suggesting that inhibition of inflammatory response may be the potential mechanism of Wendan Decoction in treating GAD. 57,61 The PPI results reveal that IL-6, TNF, SRC and AKT1 are the key targets of WDD in the treatment of GAD. KEGG enrichment analysis suggests that mechanism of WDD for GAD treatment is closely correlated with neuroactive ligand receptor interaction, calcium signaling pathway, cAMP signaling pathway, PI3K/AKT signaling pathway and MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS found that all these molecules were present in the aqueous extract of WDD we prepared. After a systematic literature search, naringenin, 56 quercetin, 57 , 58 glabridin, 59 beta-sitosterol, 60 luteolin 61 , 62 of them was the candidate molecule for anxiety. Among them, the anxiolytic effects of quercetin, luteolin and narigenin are closely related to the inhibition of inflammatory response, suggesting that inhibition of inflammatory response may be the potential mechanism of Wendan Decoction in treating GAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation